A study on the relationship between training motivation factors and training effectiveness at Petronas Carigali Sdn Bhd (PCSB) / Nurul Haizat Sharifuddin - Sharifuddin, Nurul Haizat (2012)
This project paper is prepared as a fulfillment of the Bachelor of Business Administration (Hons) majoring in International Business. The objective of this study was to find out whether is there any relationship between training motivation factors and training effectiveness. The study examines the influence of training motivation factors towards training effectiveness. In particular, training motivation factors such as personal related needs, job related needs, training reputation, training design and option to voluntary attendance are the key factors of training motivation. The study was carried out on a sample of 70 respondents of technical staff at Petronas Carigali Sdn Bhd. The data was analyzed using SPSS version 17.0. The finding shows that the independent variables which are personal related needs, job related needs, training design, training reputation, and option to voluntary attendance were very significant and related to training effectiveness.